Liver Dysfunction as a Novel Player in Alzheimer’s Progression: Looking Outside the Brain - Estrada, Lisbell D.; Ahumada, Pablo; Cabrera, Daniel; Arab, Juan P. (Frontiers in Aging Neuroscience, 2019)
Alzheimer’s disease (AD) afflicts an estimated 20 million people worldwide and is the fourth-leading cause of death in the developed world. The most common cause of dementia in older individuals, AD is characterized by neuropathologies including synaptic and neuronal degeneration, amyloid plaques, and neurofibrillary tangles (NTFs). Amyloid plaques are primarily composed of amyloid-beta peptide (Aβ), which accumulates in the brains of patients with AD. Further, small aggregates termed Aβ oligomers are implicated in the synaptic loss and neuronal degeneration underlying early cognitive impairments. Whether Aβ accumulates in part because of dysregulated clearance from the brain remains unclear. The flow of substances (e.g., nutrients, drugs, toxins) in and out of the brain is mediated by the blood-brain-barrier (BBB). The BBB exhibits impairment in AD patients and animal models. The effect of BBB impairment on Aβ, and whether BBB function is affected by non-neurological pathologies that impair peripheral clearance requires further investigation. In particular, impaired peripheral clearance is a feature of nonalcoholic fatty liver disease (NAFLD), a spectrum of liver disorders characterized by accumulation of fat in the liver accompanied by varying degrees of inflammation and hepatocyte injury. NAFLD has reached epidemic proportions, with an estimated prevalence between 20% and 30% of the general population. This chronic condition may influence AD pathogenesis. This review article summarizes the current state of the literature linking NAFLD and AD, highlighting the role of the major Aβ efflux and clearance protein, the LRP-1 receptor, which is abundantly expressed in liver, brain, and vasculature.